KOMPARASI NILAI INDEKS FAKTOR PANJANG DAN KEMIRINGAN LERENG PADA BEBERAPA DATA DIGITAL ELEVATION MODEL RESOLUSI MENENGAH - Faisol, Arif; Mashudi, Mashudi; Bachri, Samsul (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Several erosion prediction models use slope length and slope steepness factors (LS) as one of the parameters. Some researchers have developed algorithms to analyze LS based on Digital Elevation Model (DEM) data. This study aims to compare the LS based on the medium resolution of DEM data, i.e Space Shuttle Radar Topography Mission (SRTM), ASTER Global DEM, Jaxa's Global ALOS 3D World, and Copernicus DEM at 2 (two) watersheds in Manokwari, West Papua. The LS was calculated using the Desmet - Govers method. The research showed that LS analyzed using Copernicus DEM provided higher values than LS generated from SRTM DEM, ASTER Global DEM, and Jaxa's Global ALOS 3D World, meanwhile, LS generated from ASTER Global DEM data provided lower values. Furthermore, the LS value from the analysis of the Desmet - Govers method and the SRTM, ASTER Global DEM, Jaxa's Global ALOS 3D World, and Copernicus DEM have significant differences with weak to moderate correlation based on the F test and Pearson correlation test